Development of Power Semiconductor Devices Database for Knowledge-Based Systems - Shaheen, Ghassan Mohammed (2000)
Since 1970, various types of power semiconductor devices have been developed and become commercially available. Meanwhile database management and expert systems have been used in the field of power electronics for various applications. The large available number of power semiconductor devices makes it difficult to compare their numerical ratings such as voltage, current ratings and switching frequency. The objective of this thesis is to develop a database system for the power semiconductor devices in order to build the power electronics design aided system (PEDAS). PEDAS is a knowledge-based system for power electronic circuits that enable the user to get a suitable solution for the design problem through an attractive interface. The devices database system is an important and essential part of PEDAS. Using the devices database system, the user is able to get the suitable device available in the PSPICE simulation package and use its model for the design problem through a simple and attractive interface. The user can also get a comprehensive information about most of the power semiconductor devices commercially available by accessing the devices data sheets. A three-phase inverter was designed and simulated to illustrate the use of the devices database system. The inverter was designed using 1800 and 1200 conduction angle. 5kW-output power was achieved using 120V DC voltage source. The devices database system was used successfully by some of the researchers of the electrical engineering department in the Control and Automation System Centre (CASC).